1998
DOI: 10.1191/026921698676924076
|View full text |Cite
|
Sign up to set email alerts
|

Specialist palliative care in nonmalignant disease

Abstract: The objective of this study was to investigate how many patients who die from causes other than cancer might benefit from specialist palliative care. This was achieved by secondary analysis of data from the Regional Study of Care for the Dying, a retrospective national population-based interview survey. The investigation involved 20 self-selected English health districts, nationally representative in terms of social deprivation and most aspects of health services provision. A total of 3696 patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
25

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 18 publications
5
94
0
25
Order By: Relevance
“…109 Older people are proportionally more likely to die from conditions other than cancer and hence are disadvantaged by diagnosis in terms of access to specialist palliative care. 3 The findings also suggest that there are particular barriers to making the transition to a palliative care approach for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…109 Older people are proportionally more likely to die from conditions other than cancer and hence are disadvantaged by diagnosis in terms of access to specialist palliative care. 3 The findings also suggest that there are particular barriers to making the transition to a palliative care approach for people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 This philosophy of generalization of palliative care independent from the underlying disease is emphasized again by the current World Health Organization (WHO) definition. 6 Accordingly, expertise within palliative care is focussing on needs rather than disease, and it has been suggested that there is a common pathway at the end of life independent from the underlying illness.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, palliative care services have increasingly recognised the needs of non-cancer patients, 2,3 especially in rapidly fatal neurological conditions such as motor neurone disease (MND). 4,5 However, there are some major differences between the palliative care needs of people with LTNC and those of people with cancer.…”
Section: Introductionmentioning
confidence: 99%